Reputasi Korporat di Tangan Digital: Strategi Komunikasi Efektif untuk Membangun Kepercayaan dan Investasi - Rafi, Praditya Fadhlurahman; Ayuningtyas, Fitria (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to analyze corporate reputation communication strategies in digital media, focusing on PT Bank Rakyat Indonesia (Persero) Tbk (BRI). As digital media develops as the main communication platform, corporate reputation is increasingly shaped by narratives conveyed in cyberspace. The main focus of this study is to explore how digital media influences the formation of BRI's image, as well as how these perceptions can influence investment decisions, both by individual and institutional investors. The online news articles analyzed cover topics such as BRI's commitment to financial inclusion, the bank's digital transformation, and its contribution to supporting the development of small and medium-sized enterprises (SMEs). The results of the study show that digital media plays a very important role in framing BRI's reputation, with an emphasis on the values of innovation, sustainability, and corporate social responsibility. The elements of reputation identified in this study include strong financial performance, successful digital transformation, and the ability to manage and support MSMEs. These elements have proven to be key factors in building investor confidence, which in turn plays an important role in influencing market perceptions of BRI. This study makes an important contribution to understanding how digital communication strategies can be used to manage corporate reputation amid the challenges and advances of information technology, as well as their impact on investor behavior in the capital market.